The legal nature and substantive consequences of the records in section ‘IIdentification of real estate’ in the mortgage register - Kucharczuk, Ivo (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2013)
The article deals with the controversies concerning the legal nature of the records in section ‘I- Identification of real estate’ in the mortgage register, which implicitly determine the reach of the rights disclosed in other sections, and may be of importance for both the legal presumptions pertaining to these rights and the principle of public credibility of the register. Having discussed the administrative regulation of the land and building register as well as procedural mechanisms for making records in section I of the mortgage register, the author continues to analyze the view of the doctrine on the legal importance of factual data in this section, divided according to their effect on the principle of public credibility and legal presumptions of the mortgage register.